39th AIAA Thermophysics Conference 2007
DOI: 10.2514/6.2007-3903
|View full text |Cite
|
Sign up to set email alerts
|

Hypersonic Aerothermodynamics Analysis Across Nonequilibrium Regimes Using Continuum and Particle Methods

Abstract: Hypersonic vehicles experience different flow regimes during flight due to changes in atmospheric density. Computational Fluid Dynamics (CFD) is not physically accurate in areas of highly non-equilibrium flows. The direct simulation Monte Carlo (DSMC) method, while physically accurate for all flow regimes, is relatively computationally expensive. In a continuing effort to understand the performance of CFD and DSMC in hypersonic flows, the current study investigates the effect of non-equilibrium on surface aero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 25 publications
0
22
0
Order By: Relevance
“…A more recent study by Lofthouse et al examined the effects of velocity slip and temperature jump at the surface of a 2-D 12-in.-diam cylinder in Mach 10 and 25 flow of argon [9]. Another study by Lofthouse et al investigated Mach 10 and 25 nitrogen flow over a cylinder [10]. All of these studies were conducted over a range of Knudsen numbers, 0.002-0.25, in which the characteristic length is taken to be the diameter of the cylinder.…”
Section: Nomenclaturementioning
confidence: 99%
“…A more recent study by Lofthouse et al examined the effects of velocity slip and temperature jump at the surface of a 2-D 12-in.-diam cylinder in Mach 10 and 25 flow of argon [9]. Another study by Lofthouse et al investigated Mach 10 and 25 nitrogen flow over a cylinder [10]. All of these studies were conducted over a range of Knudsen numbers, 0.002-0.25, in which the characteristic length is taken to be the diameter of the cylinder.…”
Section: Nomenclaturementioning
confidence: 99%
“…Previous work by the authors comparing CFD and DSMC focused purely on numerical results, with CFD simulations being compared directly to DSMC simulations. [7][8][9][10] In particular, the walls were assumed to be fully diffusive; that is, the gas molecules colliding with the wall were assumed to accommodate fully to the wall conditions. Hence, an accommodation coefficient of unity was used for the CFD slip boundary conditions.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that the probability can better correspond with theory by multiplying by a simple factor that is dependent on the maximum temperature. 6 Unfortunately, this method does not work for multiple species and in fact was only employed for N 2 -N 2 vibrational relaxation. 7 For multiple species, a more elegant solution has been included in the DSMC method to be able to obtain the proper vibrational relaxation rate.…”
Section: A Vibrational Relaxationmentioning
confidence: 99%
“…It was also observed that velocity slip and temperature jump boundary conditions improved the agreement between the two numerical methods. Another study by Lofthouse et al 6 investigated Mach 10 and 25 nitrogen flow over a two-dimensional cylinder. That study was again conducted over a range of Knudsen numbers from continuum to rarefied flow.…”
Section: Introductionmentioning
confidence: 99%